If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 52(x + y) = 0 (x * 52 + y * 52) = 0 (52x + 52y) = 0 Solving 52x + 52y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-52y' to each side of the equation. 52x + 52y + -52y = 0 + -52y Combine like terms: 52y + -52y = 0 52x + 0 = 0 + -52y 52x = 0 + -52y Remove the zero: 52x = -52y Divide each side by '52'. x = -1y Simplifying x = -1y
| 3(b+2)=3b+2 | | 25-(x/3)=(x/2) | | 75=11+16p | | x+3(-x+1)=9 | | x^2+6x+5=x^2 | | 8t^2=32 | | n+3.01+3n=4n+3.01 | | 7.7=2.7+5x | | 30=3h+6 | | -8c=144 | | m/30=12/72 | | n+-9=-30 | | 2(2x+1)=-1o | | 2x-5-7x+1=4x-6x+11 | | Log(9)2+log(9)(X+2)=1 | | 2x+8=6x-10 | | 10+x=5-20 | | 18=7x+3-4x | | 2(-7+2y)+3y=0 | | 3(2x-3)=7x+21 | | Y=5x-0.5x | | 10000=x^2+x | | -6(10-4r)=-3(-12-8f) | | 10x+7-2x=x-2+8x | | 10x+7=x-2+8x | | 12-10(5x+4)+4x= | | 16*5*3.14= | | 3.14*16*5= | | 6b+4-2b=6b | | (2x+8)(3x+24)=0 | | 90+x+34+x+64=180 | | -6x^3+9x^2+6x= |